PENGAKUAN TANDATANGAN PADA DOKUMEN ELEKTRONIK DALAM PEMBUKTIAN HUKUM ACARA PERDATA DI INDONESIA - Fransiscus Xaverius Vincent Roger Letsoin (Faculty of Law, Universitas Pattimura, 2010)
The use of an electronic signature on an electronic document may guarantee he security of an electronic information message, using public network, because the electronic is created based on the asymmetric cryptography technology. From the research, there are some opinion disagreements concerning the authentication power of electronic documents signed with electronic signatures, used as prof in the court. The government should immediately legalized the Government Ordinance concerning Electronic Signature and Government Ordinance concerning Electronic Signature and Government Ordinance concerning Electronic Certification, there will be a through legal regulation of the Act Number 11 Year 2008.